(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Microfinance in Venezuela still not reach the level of development exhibited in other Latin American countries, as in the case of Bolivia, Ecuador and Colombia, despite being recognized and documented its importance in the struggle to incorporate the population with the lowest income economic progress. In that line, this research was to investigate the dynamics north of microfinance in Venezuela for the period 2002-2012, in terms of the structure of the banking system and financial depth of it in relation to the development of economic activity or development of Gross Domestic Product. The choice of starting year of the series is marked by the fact that the year from which you are obliged by the traditional banking finance, initially with 1 and then 3% of your portfolio, microenterprise activities. In view of the nature documentary and / or monograph of the subject here treated, methodologically demand the use of secondary data sources, national and international, as in the case of the balance press the Superintendence of Banks for the national event and MixMarket, ECLAC and IDB / MIF for the international event. The results reveal microcredit marginalization with respect to total credit and a decreasing trend in their development. International comparison of the penetration of microcredit also reveals marginalization with respect to the Latin American context.